Exploring level of awareness of small and medium sized enterprises towards goods and services tax implementation in Malaysia / Ely Raziah Abdul Rashid , Nor Farizal Mohammed and Norhasnah Mohd Saheh - Abdul Rashid, Ely Raziah; Mohammed, Nor Farizal; Mohd Saheh, Norhasnah (Institute of Research, Development and Commercialization (IRDC), 2005)
The Prime Minister, Datuk Seri Abdullah Badawi announced the proposed implementation of Goods and Services Tax (GST) in Malaysia during 2005 Budget speech with effect from 1st January 2007. The announcement has since received mixed responses from the public, business community, tax practitioners and experts as well as academicians. One of the much debated issues is the heavy administrative burden GST would have on Small and Medium Sized Enterprises (SMEs). GST compliance will require SMEs to make sure that they have a good accounting system to ensure GST paid and collected are correctly documented. This compliance job is seen as a big issue for SMEs on top of coping with their day-to-day business survival. However, some practitioners are of the opinion that the real issue is awareness. Awareness contributes not only towards readiness but also potential support for the new tax system. Businesses are unlikely to accept or support a change in the tax system without being made aware of the implications it has on their businesses.